Multiparametric magnetic resonance imaging including oxygenation mapping of experimental ischaemic stroke. Issue 6 (June 2017) - Boisserand, Ligia Simões Braga; Lemasson, Benjamin; Hirschler, Lydiane; Moisan, Anaïck; Hubert, Violaine; Barbier, Emmanuel L; Rémy, Chantal; Detante, Olivier
Recent advances in MRI methodology, such as microvascular and brain oxygenation (StO2 ) imaging, may prove useful in obtaining information about the severity of the acute stroke. We assessed the potential of StO2 to detect the ischaemic core in the acute phase compared to apparent diffusion coefficient and to predict the final necrosis. Sprague-Dawley rats (n = 38) were imaged during acute stroke (D0) and 21 days after (D21). A multiparametric MRI protocol was performed at 4.7T to characterize brain damage within three region of interest: 'LesionD0' (diffusion), 'Mismatch' representing penumbra (perfusion/diffusion) and 'Hypoxia' (voxels < 40% of StO2 within the region of interest LesionD0). Voxel-based analysis of stroke revealed heterogeneity of the region of interest LesionD0, which included voxels with different degrees of oxygenation decrease. This finding was supported by a dramatic decrease of vascular and perfusion parameters within the region of interest hypoxia. This zone presented the lowest values of almost all parameters analysed, indicating a higher severity. Our study demonstrates the potential of StO2 magnetic resonance imaging to more accurately detect the ischaemic core without the inclusion of any reversible ischaemic damage. Our follow-up study indicates that apparent diffusion coefficient imaging overestimated the final necrosis while StO2 imaging did not.